2010
DOI: 10.3324/haematol.2009.018259
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of human Hb switching: a possible role of the kit receptor/miR 221-222 complex

Abstract: BackgroundThe human hemoglobin switch (HbF→HbA) takes place in the peri/post-natal period. In adult life, however, the residual HbF (<1%) may be partially reactivated by chemical inducers and/or cytokines such as the kit ligand (KL). MicroRNAs (miRs) play a pivotal role in normal hematopoiesis: downmodulation of miR-221/222 stimulates human erythropoietic proliferation through upmodulation of the kit receptor. Design and MethodsWe have explored the possible role of kit/KL in perinatal Hb switching by evaluatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…miR-15a and miR-16-1 also have been reported to elevate fetal hemoglobin expression in human trisomy 13 via MYB (20). In addition, the kit receptor/miR-221-222 complex may be involved in human hemoglobin switching (30). miR-210 has also been identified to be involved with the increased expression of the ␥-globin genes in differentiating erythroid cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…miR-15a and miR-16-1 also have been reported to elevate fetal hemoglobin expression in human trisomy 13 via MYB (20). In addition, the kit receptor/miR-221-222 complex may be involved in human hemoglobin switching (30). miR-210 has also been identified to be involved with the increased expression of the ␥-globin genes in differentiating erythroid cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…Increased miRNA-210 levels elevated Ǒ-globin levels in hereditary persistence of HbF (Bianchi et al, 2009), while the let-7 family has been associated with hemoglobin switching (Noh et al, 2009). Recently, two miRNAs, miR-221 and miR-222, have been identified to regulate HbF expression in erythropoietic cells via the kit receptor (Gabbianelli et al, 2010). miRNA-150 repression of MYB in hematopoietic progenitor cells, of human bone marrow origin, supported MYB's importance in erythroid and megakaryocytic differentiation (Lu et al, 2008).…”
Section: Other Factors That Participate In Hemoglobin Switchingmentioning
confidence: 99%
“…Some authors indicated that Hb switching (HbF→HbA) is controlled by miRNA-221/222 complex and its overexpression caused an inhibitory effect on erythroid cell proliferation [71]. The exact molecular mechanisms controlling miRNA-221/222 expression were not well known.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The exact molecular mechanisms controlling miRNA-221/222 expression were not well known. Gabbianelli et al speculated that other mechanisms such as glucocorticoids and the transcription factor BCL11A could also contribute to the fetal-adult Hb switch [71]. Kouhkan et al.…”
Section: Accepted Manuscriptmentioning
confidence: 99%